Gaston Bachelard e il “ritardo della psicoanalisi” - Del Longo, Nevio (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2022)
The article highlights how Bachelard criticised the psychoanalysis of the time which was too conditioned to “discover” and “interpret” rather than to live the artistic gesture and imagination in its astonishment and retentissement. The relationship between Bionian and post-Bionian psychoanalysis is then shown, along with how Bachelard anticipated its themes both through the attitude of free and participatory listening and through rêverie, arriving a few decades earlier at the conclusion that imagination and in particular rêverie and the creative and imaginative act are a healthy function of the human being and not the result of infantile fixations or emotional discharges.